The Impact of Social Media on Consumer Decision-Making: An Experimental Study - Ramadani Saputra; Nugroho Widianto (Jurnal Office, 2021)
Social media has become a prominent platform for businesses to promote their products and services. However, the impact of social media on consumer decision-making in Indonesia remains unclear. This study aims to investigate the impact of social media on consumer decision-making in Indonesia. An experimental study was conducted on a sample of 100 participants who were exposed to social media advertisements and traditional advertisements. The participants were then asked to make a purchase decision, and their responses were analyzed. The findings of this study indicate that social media has a significant impact on consumer decision-making in Indonesia. Participants who were exposed to social media advertisements were more likely to make a purchase compared to those who were exposed to traditional advertisements.